TRADISI WIRID YASIN PADA MASYARAKAT SUKU MELAYU DALAM PERSPEKTIF PENDIDIKAN ISLAM - Mardiyahdiyah; Jarir; Taufik; Abdul wahab (EL-TA’DIB: Journal of Islamic Education, 2025)
The Yasin recitation tradition is a deeply rooted religious practice in Muslim communities, particularly in Indonesia. This activity is typically performed routinely in mosques, prayer rooms (surau), and homes, involving the recitation of Surah Yasin, tahlil (recitation of the Quran), and communal prayer. From an Islamic educational perspective, this tradition is not merely a ritual worship but also a means of moral, spiritual, social, and cultural development for Muslims. This article aims to examine the meaning, value, and relevance of the Yasin recitation tradition in shaping the character and religious awareness of the Muslim community. The Wirid Yasin tradition is a religious practice deeply rooted in the life of the Malay ethnic group. Beyond being a spiritual ritual, this tradition contains significant educational dimensions. This study aims to uncover the Islamic educational values contained within the Wirid Yasin tradition. Using a descriptive qualitative method, the research findings indicate that Wirid Yasin is not merely the recitation of holy verses, but a means of internalizing the values of aqidah (faith), ukhuwah Islamiyah (Islamic brotherhood), and character education (akhlak). This tradition functions as an effective non-formal educational institution in maintaining social cohesion and the spiritual strengthening of the Malay community. Keywords: Wirid Yasin, Malay Tribe, Islamic Education, Character Values.